Inflammation‐induced foam cell formation in chronic inflammatory disease. Issue 8 (10th March 2015) - Angelovich, Thomas A; Hearps, Anna C; Jaworowski, Anthony
Abstract : Atherosclerosis is the leading cause of cardiovascular disease and is both a metabolic and inflammatory disease. Two models describe early events initiating atherosclerotic plaque formation, whereby foam cells form in response to hyperlipidaemia or inflammation‐associated stimuli. Although these models are inextricably linked and not mutually exclusive, identifying the unique contribution of each in different disease settings remains an important question. Circulating monocytes are key mediators of atherogenesis in both models as precursors to lipid‐laden foam cells formed in response to either excess lipid deposition in arteries, signalling via pattern‐associated molecular patterns or a combination of the two. In this review, we assess the role of monocytes in each model and discuss how key steps in atherogenesis may be targeted to enhance clinical outcomes in patients with chronic inflammatory disease.